Uncovering Mathematical Literacy Ability of Eighth Grade Junior High School Students Based on VARK Learning Style - Chairuddin; Sari, Dian Ulfa; Salido, Achmad; Febrian , Fadri (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2025)
Abstract: This study explores the mathematical literacy skills of eighth-grade students based on their learning styles using the VARK model (Visual, Auditory, Read/Write, Kinesthetic). A descriptive qualitative approach was employed, involving 23 junior high school students in one of the districts in Southeast Sulawesi, Indonesia. Five informants representing auditory, read/write, kinesthetic, auditory-read/write-kinesthetic, and visual-read/write-kinesthetic types were selected through purposive sampling. Data were collected through mathematical literacy tasks and unstructured interviews. The findings reveal that learning styles influence mathematical literacy, including communication, modeling, representation, and problem-solving skills. Auditory learners excelled in all stages, while read/write and kinesthetic learners struggled, particularly in communication and problem-solving. Multimodal learners demonstrated greater flexibility. Abstrak: Penelitian ini mengeksplorasi keterampilan literasi matematika siswa kelas VIII berdasarkan gaya belajar mereka menggunakan model VARK (Visual, Auditori, Membaca/Menulis, Kinestetik). Pendekatan kualitatif deskriptif digunakan dengan melibatkan 23 siswa SMP di salah satu kabupaten yang ada di Sulawesi Tenggara, Indonesia. Selanjutnya, lima siswa dipilih secara purposive sampling sebagai informan penelitian mewakili gaya belajar tipe auditori, membaca/menulis, kinestetik, auditori membaca/menulis-kinestetik, dan visual-membaca/menulis-kinestetik. Pengumpulan data dilakukan melalui tugas literasi matematika dan wawancara tidak terstruktur. Hasil penelitian menunjukkan bahwa gaya belajar memengaruhi literasi matematika, termasuk kemampuan komunikasi, pemodelan, representasi, dan pemecahan masalah. Siswa auditori unggul dalam semua tahapan, siswa dengan gaya belajar membaca/menulis dan kinestetik mengalami kesulitan terutama dalam komunikasi dan pemecahan masalah, sementara pembelajar multimodal lebih fleksibel.